Peri-conceptional diet patterns and the risk of gestational diabetes mellitus in South Indian women. Issue 4 (27th April 2023) - Mahendra, Anvesha; Kehoe, Sarah H; Crozier, Sarah R; Kumaran, Kalyanaraman; Krishnaveni, GV; Arun, Nalini; Padmaja,; Kini, Prakash; Taskeen, Unaiza; Kombanda, Krupa T; Johnson, Matthew; Osmond, Clive; et al.
Abstract: Objective: To identify peri-conceptional diet patterns among women in Bangalore and examine their associations with risk of gestational diabetes mellitus (GDM). Design: BAngalore Nutrition Gestational diabetes LifEstyle Study, started in June 2016, was a prospective observational study, in which women were recruited at 5–16 weeks' gestation. Peri-conceptional diet was recalled at recruitment, using a validated 224-item FFQ. GDM was assessed by a 75-g oral glucose tolerance test at 24–28 weeks' gestation, applying WHO 2013 criteria. Diet patterns were identified using principal component analysis, and diet pattern–GDM associations were examined using multivariate logistic regression, adjusting for ' a priori ' confounders. Setting: Antenatal clinics of two hospitals, Bangalore, South India. Participants: Seven hundred and eighty-five pregnant women of varied socio-economic status. Results: GDM prevalence was 22 %. Three diet patterns were identified: (a) high-diversity, urban (HDU) characterised by diverse, home-cooked and processed foods was associated with older, more affluent, better-educated and urban women; (b) rice-fried snacks-chicken-sweets (RFCS), characterised by low diet diversity, was associated with younger, less-educated, and lower-income, rural and joint families; and (c) healthy, traditional vegetarian (HTV), characterised by home-cooked vegetarian and non-processed foods, was associated with less-educated, more affluent, and rural and joint families. The HDU pattern was associated with a lower GDM risk (adjusted odds ratio (aOR): 0·80/sd, 95 % CI (0·64, 0·99), P = 0·04) after adjusting for confounders. BMI was strongly related to GDM risk and possibly mediated diet–GDM associations. Conclusions: The findings support global recommendations to encourage women to attain a healthy pre-pregnancy BMI and increase diet diversity. Both healthy and unhealthy foods in the patterns indicate low awareness about healthy foods and a need for public education.